Qingjie Fuzheng Granule Inhibits EMT and Induces Autophagy in Colorectal Cancer via mTOR Signaling Pathways. (30th November 2021) - Zhu, Xiaoqin; Chen, Yongan; Lin, Minghe; Huang, Bin; Lin, Jiumao
Abstract : Qingjie Fuzheng granule (QFG) is a traditional Chinese medicinal formula used extensively as an alternative medicine for cancer treatment, including colorectal cancer (CRC). But its pathological mechanism in CRC is unclear. To study antitumor treatment effects and mechanisms of QFG, we established a CRC HCT-116 xenograft mouse model and assessed QFG on EMT and autophagy progression in vivo. The mice were randomly divided into 2 groups ( n = 10 each group) and treated with intragastric administration of 1 g/kg of QFG or saline 6 days a week for 28 days (4 weeks). Body weight was measured every other day with electronic balance. At the end of the treatment, the tumor weight was measured. Immunohistochemical (IHC) and western blot (WB) assay were used to detect the expression level of E-cadherin, N-cadherin, vimentin, and TWIST1 to evaluate the effect of QFG on tumor cell EMT progression. IHC and WB assay were also used to detect the expression level of beclin-1, LC3-II, and p62 to evaluate the effect of QFG on tumor cell autophagy progression. Furthermore, the expression level of relative proteins in mTOR pathway was detected by WB assay to investigate the mechanism of QFG effect on CRC. We discovered that QFG inhibited the rise of tumor weight while it had no effect on mice body weight, which proved that QFG could inhibit CRC growth progression without significant side effects in vivo. In addition, QFG treatment inhibited EMT and induced autophagy progression in CRC tumor cells, including that QFG upregulated the expression of E-cadherin, beclin-1, and LC3-II, but downregulated the expression of N-cadherin, vimentin, TWIST1, and p62. And, QFG decreased the ratio of p-PI3K/PI3K, p-AKT/AKT, and p-mTOR/mTOR, but increased the ratio of p-AMPK/AMPK. All findings from this research proved that QFG can induce autophagy and inhibit EMT progression in CRC via regulating the mTOR signaling pathway.